Memory Activity Test Of Ethanol Extract Of Oil Palm Leaves (Elaeis Guineensis Jacq.) On White Mice (Mus Musculus) With Radial Arm Maze Method - Nadia; Bagas Ardiyantoro; Septian Maulid Wicahyo (International Journal of Health Engineering and Technology, 2026)
Memory loss is a cognitive disorder in which oxidative stress is one of the main contributing factors. Palm leaves oil (Elaeis guineensis Jacq.) contains flavonoids and antioxidants that are believed to improve memory. This study aims to determine whether oil palm leaf extract can improve memory activity in mice and determine the most effective dosage. This study was a pure experimental study with 25 mice divided into five groups, namely negative control (CMC Na 1%), positive control (Ginkgo biloba), and treatment groups with ethanol extracts of oil palm leaves at doses of 100 mg/kgBW, 200 mg/kgBW, and 300 mg/kgBW. The mice were induced with 10% alcohol and then given treatment for 7 days. Memory activity was tested using the Radial Arm Maze method, with parameters measured including latency time and error rate. The data obtained were then analyzed using SPSS, including normality and homogeneity tests, Anova, and followed by the Tukey test. The results showed that doses of palm leaf extract (Elaeis guineensis jacq.) of 100 mg/kgBW, 200 mg/kgBW, and 300 mg/kgBW had an effect on the memory of mice. The effective dose for improving memory in the T1-T2 latency time difference was 200 mg/kgBW and 300 mg/kgBW with a P value > 0.05, which was not significantly different from the positive control, and the T1-T2 error rate difference was 100 mg/kgBW, 200 mg/kgBW, and 300 mg/kgBW, with a P value > 0.05, showing no significant difference from the positive controls. This proves that oil palm leaf extract can enhance memory activity in mice.